Another view: an analysis of embodied interactions and performative arts-based practices at Driekopseiland. - Slabolepszy, Frances (My University, 2018)
At the very centre of the map of South Africa, just outside Kimberley in the Northern Cape, is a place now known as Driekopseiland. This rock art site is comprised of more than three and a half thousand images that have been pecked or engraved into the rock that forms the bed of the Riet River. Research into the site has spanned hundreds of years, but has frequently focused attention on who the engravings were made by, as a result of their unusual style. Traditional archaeological methods are considered, detailed and rigorous, but they also have to be focused on answering certain questions and throughout the history of research of this site, these questions have frequently been limited to who created the engravings. After being introduced to the site by archaeologist Professor David Morris, I have extended Morris’ call for a new interpretation, or a new way to view the site, by drawing on techniques from arts-based disciplines to suggest another way of interacting with the site for researchers and visitors. As a student of Heritage Studies I explore how this site constitutes a South African heritage site and what implications this has for the way it is studied, protected and shared with the public. Following this, I argue that specific arts-based approaches offer another way to view heritage sites as experiential and embodied, and that this approach can deepen and enrich the visitor experience. And further, that particularly in a case like Driekopseiland, where aspects of the site’s origin are still inconclusive from an archaeological point of view, arts-based approaches that place an emphasis on personal process, have the potential to open the site up to new possibilities of understanding for researchers and visitors. I define an arts-based, embodied engagement as one that places an emphasis on how researchers interact with the site on a physical level and how this affects what they see, hear and learn. In this research report I investigate how researchers’ physical interactions with heritage sites such as the rock art at Driekopseiland contribute to our understanding of it. Through my analysis of the interactions conducted by me and three other arts practitioners during my fieldwork, I illustrate the insights gained through an approach that makes use of techniques from theatre, visual arts and film. This research report considers how arts-based practices that place an emphasis on processes of interaction and embodiment at the site can help engender a sense of connection with and responsibility for the site, which may in turn impact how we experience other heritage sites in South Africa.
A thesis submitted in fulfilment of the requirement for the degree Master of Arts in Heritage to the to the Faculty of Humanities,University of the Witwatersrand, Johannesburg, 2018
Keywords: Rock paintings; Historic sites--South Africa; Art, Prehistoric